2020
DOI: 10.1002/rth2.12421
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring standard and extended half‐life products in hemophilia: Assay discrepancies for factor VIII and IX in pre‐ and postinfusion samples

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…In the current study, we used a different APTT reagent, containing ellagic acid instead of silica as activator, and a different coagulation analyser (Atellica Coag 360). These modifications make a direct comparison to the former study 9 difficult. However, the CSA‐1 reagent and calibrator were still the same, but the overestimation was less at high levels on the new instrument.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In the current study, we used a different APTT reagent, containing ellagic acid instead of silica as activator, and a different coagulation analyser (Atellica Coag 360). These modifications make a direct comparison to the former study 9 difficult. However, the CSA‐1 reagent and calibrator were still the same, but the overestimation was less at high levels on the new instrument.…”
Section: Discussionmentioning
confidence: 96%
“…The strength of our study is that several products were tested under similar and comparable measurement conditions (instrument, reagent lots, calibration curves, etc.). As evaluated recently, a large assay discrepancy between FVIII CSA and OSA in post‐infusion samples was revealed 9 . In the current study, we used a different APTT reagent, containing ellagic acid instead of silica as activator, and a different coagulation analyser (Atellica Coag 360).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…43 In contrast to the OSCA results, higher results for rFVIIIFc are obtained when samples are analysed by CSAs. 35,[42][43][44] It was assumed that these discrepancies stem from differences between the WHO IS for FVIII concentrate or plasma. 42 However, it is generally concluded that both the OSCA and the CSA may be used to safely monitor rFVIIIFc-based factor FVIII replacement therapies.…”
Section: Efmoroctocog Alfa (Elocta)mentioning
confidence: 99%